Ebola Virus Infection: Overview and Update on Prevention and Treatment. Issue 4 (December 2015) - Martínez, Miguel; Salim, Abdulbaset; Hurtado, Juan; Kilgore, Paul
Abstract In 2014 and 2015, the largest Ebola virus disease (EVD) outbreak in history affected large populations across West Africa. The goal of this report is to provide an update on the epidemic and review current progress in the development, evaluation and deployment of prevention and treatment strategies for EVD. Relevant information was identified through a comprehensive literature search using Medline, PubMed and CINAHL Complete and using the search terms Ebola, Ebola virus disease, Ebola hemorrhagic fever, West Africa outbreak, Ebola transmission, Ebola symptoms and signs, Ebola diagnosis, Ebola treatment, vaccines for Ebola and clinical trials on Ebola. Through 22 July 2015, a total of 27, 741 EVD cases and 11, 284 deaths were reported from all affected countries. Several therapeutic agents and novel vaccines for EVD have been developed and are now undergoing evaluation. Concurrent with active case investigation, contact tracing, surveillance and supportive care to patients and communities, there has been rapid progress in the development of new therapies and vaccines against EVD. Continued focus on strengthening clinical and public health infrastructure will have direct benefits in controlling the spread of EVD and will provide a strong foundation for deployment of new drugs and vaccines to affected countries when they become available. The unprecedented West Africa Ebola outbreak, response measures, and ensuing drug and vaccine development suggest that new tools for Ebola control may be available in the near future.